PELATIHAN KEWIRAUSAHAAN UNTUK MENGEMBANGKAN UMKM DESA WIBAWAMULYA - Nurfaizi, Rizky; Pangestuti, Rinda Siaga; Qintharah, Yuha Nadhirah (Universitas Islam 45 Bekasi, 2024)
Entrepreneurship training is training that can train participants in stages to have entrepreneurial and business competencies, train entrepreneurs and the business world, train entrepreneurs to be able to act in establishing a viable business by taking advantage of the opportunities that exist at a certain time. And in certain fields as well as developing human resources capable of creating jobs for themselves and others in accordance with development demands with the aim of creating motivation for participants so that they can improve quality and quantity. An entrepeneur has a role both internally, entrepreuner play a role in reducing the level of dependence on other people, increasing self-confidence and increasing the purchasing power of the perpetrator. Externally, an entrepreuner plays a role in providing job opportunities for job opportunities for seekers. By attacting the workforce through job opportunities provided by entrepreneurs, the national unemployment rate can be reduced. Training can also make Human Resources more critical, creative and have additional skills. Skills are an important component needed in various areas of life. These 21st century skills are life and career skills, learning and innovation skills, and media and information technology skills